Numerical Simulation Study on Lateral Collapse of Kenaf-Foam Composite Filled in Cylindrical Tube Subjected to Dynamic Loading - Ahmad Zaidi, Ahmad Mujahid; Ling Lang, Goh; Ahmad Zaidi, Ahmad Firdaus (Journal of Science and Technology, 2010)
In this paper the energy absorption of kenaf foam filled cylindrical tube has been investigated. First, a finite element model for empty cylindrical tube was constructed and followed by a foam-filled cylindrical tube model. In this study, there were five samples of kenaf foam density that been used and they are 5%, 10%, 15%, 20% and 0% (100%PU) for three different thickness cylindrical tube. The implemented models were used to simulate the behavior of empty and foam-filled tubes under lateral dynamic loadings. An impact mass of 10kg with three different impact velocity, 10m/s, 15m/s and 20m/s were used in the empty tube model simulation. Meanwhile, for foam-filled tube, impact velocity had increased to10m/s, 20m/s and 30m/s. The energy absorption capability was increased with foam filler in the cylindrical tube and the best kenaf foam density was obtained at 15%. For 15% kenaf foam, the value of energy absorption was higher than 100% PU but the energy absorption decreases for 20%.The results showed that increases wall thickness and kenaf foam filler will increase the energy absorption.